2015
DOI: 10.1515/cer-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Financial And Non-financial Factors Motivating Individual Donors To Support Public Benefit Organizations

Abstract: This study is aimed at determining how the financial data of public benefit organizations (PBOs) affects donations received by them and if the donors use financial and non-financial information in order to donate. In order to achieve our aim we used different methods of research: quantitative research (econometric model and survey) and qualitative research (laboratory test). The research allowed us to draw the conclusion that Polish donors make very limited use of PBOs’ financial statements in the dona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Research on donors' perceptions reveals their interest in both financial and non-financial information [4,14,16]. Waniak-Michalak and Zarzycka [15] showed that Polish donors consider information about the organisation's goals and descriptions of its projects to be more useful than financial information. Saxton et al find [17] a positive relationship between the level of donations made to US non-profits and the quantity of information these organisations provide through the web.…”
Section: Information Needs For Decision-makingmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on donors' perceptions reveals their interest in both financial and non-financial information [4,14,16]. Waniak-Michalak and Zarzycka [15] showed that Polish donors consider information about the organisation's goals and descriptions of its projects to be more useful than financial information. Saxton et al find [17] a positive relationship between the level of donations made to US non-profits and the quantity of information these organisations provide through the web.…”
Section: Information Needs For Decision-makingmentioning
confidence: 99%
“…Empirical evidence on the usefulness of non-financial information for individual donors is controversial and inconclusive. Waniak-Michalak and Zarzycka [15] point out that Polish individual donors focus on non-financial information, mainly descriptive information about objectives and projects, when selecting an organisation to donate to. On the other hand, Buchheit and Parsons [47] and Parsons [4] evidence that non-financial information (service, efforts and achievements reporting) has no significant influence on actual donations.…”
Section: Individual Private and Public Donorsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the activities of corporations and their reporting on their environmental impacts (see, Deegan & Kamal, 2013;Yongvanich & Guthrie, 2006;Roberts & Wallace, 2015), employees (Husser & Evraert-Bardinet, 2014) and product quality and safety (Dagiliene, 2010) have been widely analyzed by researchers in various countries, the philanthropic activity of corporations and NGOs and the related disclosures are presented less often. Researchers concentrate rather on the research examing the role of financial data and other information from NGOs" annual reports in influencing giving decisions (Waniak-Michalak & Zarzycka, 2015;Connolly, Hyndman and McConville, 2013;Khumawala et al, 2005;Buchheit & Parsons, 2007).…”
Section: Csr-related Cooperation Between Corporations and Ngosmentioning
confidence: 99%
“…Taking into consideration the role of public benefit organizations/charities we can see a great need to properly assess such entities. Their importance for the economy, represented for example by the volume of funds they control, requires monitoring their operations [36]. For example the average income generated by charities operating in Great Britain in 2015 was 426.3 thousand pounds whereas the average turnover in SME in 2015 amounted about 325.9 thousand pounds [3; 26].…”
Section: Introductionmentioning
confidence: 99%